Effect of cefovecin on the fecal flora of healthy dogs - Lawrence, Megan Rene (Kansas State University, 2014)
Cefovecin is an extended-spectrum long-acting third generation cephalosporin used to treat canine infections. The study objective was to determine the effect of cefovecin on the absolute number and antimicrobial susceptibility of fecal enteric bacteria in healthy dogs. Fourteen Beagles were randomly assigned to a treated (n = 7, 8 mg/kg cefovecin subcutaneously on day 1) or untreated (n = 7) group. LC/MS was used to determine plasma cefovecin concentration on day 14. E. coli, enterococci, and Salmonella were isolated and enumerated from fecal samples collected on days 0, 3, 7, 14, and 28. Antimicrobial resistance was determined using disc diffusion, MIC, and detected using PCR for the bla[subscript CMY-2] gene on select isolates. Mean plasma concentration of cefovecin on day 14 was 9.59 µg/mL in treated dogs; untreated dogs had no measurable plasma cefovecin. The absolute number of E. coli was lower in treated dogs on day 3 (P ≤ 0.0001), and the absolute number of cefovecin-resistant E. coli was higher in treated dogs on days 7 (P = 0.002), 14 (P = 0.004) and 28 (P ≤ 0.0001), compared to untreated dogs. Enterococci increased and were higher in the treatment group on day 7 (P = 0.0226). Isolation of Salmonella was rare. After cefovecin treatment, beta-lactam resistance was more common in fecal E. coli from treated dogs than untreated dogs, while resistance of enterococci was not altered. On day 28, treated dogs were 3.25 times more likely to carry the bla[subscript CMY-2] gene than untreated dogs (95% CI 1.27 – 8.35). The implications of these findings in clinically ill patients require further research.
Keywords: Cefovecin; Antimicrobial resistance; Enterococci; Gastrointestinal flora; E. coli; Microbiology (0410); Veterinary Medicine (0778)